Cord Blood Platelet Lysate-Loaded Thermo-Sensitive Hydrogels for Potential Treatment of Chronic Skin Wounds - Arianna Grivet-Brancot; Marianna Buscemi; Gianluca Ciardelli; Simona Bronco; Susanna Sartori; Claudio Cassino; Tamer Al Kayal; Paola Losi; Giorgio Soldani; Monica Boffito (Pharmaceutics)
Background/Objectives: Chronic skin wounds (CSWs) are a worldwide healthcare problem with relevant impacts on both patients and healthcare systems. In this context, innovative treatments are needed to improve tissue repair and patient recovery and quality of life. Cord blood platelet lysate (CB-PL) holds great promise in CSW treatment thanks to its high growth factors and signal molecule content. In this work, thermo-sensitive hydrogels based on an amphiphilic poly(ether urethane) (PEU) were developed as CB-PL carriers for CSW treatment. Methods: A Poloxamer 407®-based PEU was solubilized in aqueous medium (10 and 15% w/v) and added with CB-PL at a final concentration of 20% v/v. Hydrogels were characterized for their gelation potential, rheological properties, and swelling/dissolution behavior in a watery environment. CB-PL release was also tested, and the bioactivity of released CB-PL was evaluated through cell viability, proliferation, and migration assays. Results: PEU aqueous solutions with concentrations in the range 10–15% w/v exhibited quick (within a few minutes) sol-to-gel transition at around 30–37 °C and rheological properties modulated by the PEU concentration. Moreover, CB-PL loading within the gels did not affect the overall gel properties. Stability in aqueous media was dependent on the PEU concentration, and payload release was completed between 7 and 14 days depending on the polymer content. The CB-PL-loaded hydrogels also showed biocompatibility and released CB-PL induced keratinocyte migration and proliferation, with scratch wound recovery similar to the positive control (i.e., CB-PL alone). Conclusions: The developed hydrogels represent promising tools for CSW treatment, with tunable gelation properties and residence time and the ability to encapsulate and deliver active biomolecules with sustained and controlled kinetics.